The Effect of different Stocking Density on Ammonia Content (NH3) and Nitrite (NO2) in Catfish (Clarias Sp.) with Biofloc Aquaculture System - Ahmad Nizar Fanani; Boedi Setya Rahardja; Prayogo . (Journal of Aquaculture Science, 2018)
The accumulation of waste in aquaculture can cause inorganic toxins  named ammonia (NH3) and nitrite (NO2) in water. Biofloc technology is one of the new alternative to solve the problem of ammonia (NH3) and nitrite (NO2) in aquaculture techniques adapted from sewage treatment. This study aims to determine the effect of stocking density of catfish (Clarias sp.) using biofloc system against ammonia and nitrite. This study used an experimental method to completely randomized design (CRD). Statistical analysis using Analysis of Variant (ANOVA) to determine the effect of treatment.The results of the study showed that the effect of stocking density of catfish (Clarias sp.) were significantly different (P <0.05) against ammonia (NH3). The lowest average production levels of ammonia (NH3) was the PO treatment (stocking density 15 fishes/15 L) of 0.1689 ± 0.0052, and the highest was treatment P3 (stocking density 30 fishes /15 L) of 0.1819 ± 0.0016. Effect of stocking density of African catfish (Clarias sp.) was not significantly different (P> 0.05) to nitrite (NO2). The lowest average content of nitrite production (NO 2) was the PO treatment (stocking density 15 fishes/15 L) of 0.0358 ± 0.0028 and the highest was P3 treatment (stocking density 30 fishes/15 L) of 0.0388 ± 0.0042. During the culture. temperature was  26,4-29,70C, dissolved oxygen was 5.2 to 8.3 mg / L and pH between 7.01 to 8.66.   Keywords : Biofloc, ammonia, nitrite